Halide Perovskites for Applications beyond Photovoltaics. Issue 3 (25th January 2018) - Kim, Hyojung; Han, Ji Su; Choi, Jaeho; Kim, Soo Young; Jang, Ho Won
Abstract: In recent years, halide perovskites have been attracting intense attention as novel materials for photovoltaic applications due to their high carrier mobility, extraordinarily long carrier diffusion lengths, and suitable optical bandgaps. Furthermore, there are extensive applications of halide perovskites owing to their exceptional attributes in different areas, such as light‐emitting diodes, lasers, X‐ray detectors, memory devices, and more. Here, the unique characteristics of halide perovskite materials are described, including their electrical and optical properties, to explain why these materials are so exciting for a wide variety of applications. After introducing the synthesis techniques used to prepare halide perovskite films, recent advances on the applications of halide perovskites beyond photovoltaics are addressed. The challenges to be overcome for several applications are described and it is suggested that halide perovskites are equivalent to a gold standard in developing next‐generation optoelectronic and electronic devices. Abstract : Halide perovskites, with their unique characteristics such as electrical and optical properties, are reviewed for various applications beyond photovoltaics, introducing light‐emitting diodes, lasers, resistive‐switching memories, transistors, X‐ray detectors, Li‐ion batteries, piezoelectric energy generators, and gas sensors. Also, the challenges involved in these applications are presented in order to provide theoretical guidance to investigate new applications.